2017
DOI: 10.20960/nh.753
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del té verde y su contenido de galato de epigalocatequina (EGCG) sobre el peso corporal y la masa grasa en humanos. Una revisión sistemática

Abstract: The prevalence and incidence of overweight and obesity worldwide continues to increase, as well as diseases related to these conditions. This is attributed to an increase in energy intake and a decrease in energy expenditure. Consumption of green tea has been linked to a reduction in body fat and body weight. However, research on green tea has been very diverse. This review assesses the investigations that have been made with green tea and its epigallocatechin gallato (EGCG) content, evaluating its effect on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Various studies have investigated strategies to reduce body fat [1][2][3][4] to improve the physical performance of exercise practitioners and athletes [5], as well as to enhance the life quality of the population. Taurine is a free intracellular nitrogenous compound derived from methionine and cysteine, mainly found in abundance in seafood [6].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have investigated strategies to reduce body fat [1][2][3][4] to improve the physical performance of exercise practitioners and athletes [5], as well as to enhance the life quality of the population. Taurine is a free intracellular nitrogenous compound derived from methionine and cysteine, mainly found in abundance in seafood [6].…”
Section: Introductionmentioning
confidence: 99%
“…Green tea is rich in epigallocatechin gallate (EGCG). Several clinical trials have shown that EGCG assumption is associated with a statistically significant reduction in body weight, BMI and visceral fat [53][54][55][56]69]. These effects have often been studied in association with the consumption of caffeine, which seems to act in synergy with EGCG in reducing body weight [70].…”
Section: Body Weight and Body Compositionmentioning
confidence: 99%
“…The effectiveness of GT in reducing body weight and fat is widely discussed in the literature. GT derived EGCG in variable quantities (100-460 mg/day) exhibits measurable weight-loss properties in a large majority of studies according to a recent review and one meta-analysis, especially for trial durations of three or more months [43,44]. In addition, the consumption of caffeine at doses between 80 and 300 mg/day has been shown to be an important factor for these effects, when the participants did not have a high baseline caffeine intake (>300 mg/day).…”
Section: Green Teamentioning
confidence: 99%